2012
DOI: 10.1128/jb.00901-12
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of Sphingobium indicum B90A, a Hexachlorocyclohexane-Degrading Bacterium

Abstract: Sphingobium indicum B90A, an efficient degrader of hexachlorocyclohexane (HCH) isomers, was isolated in 1990 from sugarcane rhizosphere soil in Cuttack, India. Here we report the draft genome sequence of this bacterium, which has now become a model system for understanding the genetics, biochemistry, and physiology of HCH degradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 17 publications
2
29
1
Order By: Relevance
“…Furthermore, phenol/toluene and chlorophenol degradation pathways were observed in IP26 T . Unlike the genome of S. indicum B90A T (2), the draft genome assembly of IP26 T was found to have a homogentisate degradation pathway. Genes encoding putative metal resistance/efflux proteins, including resistance proteins for lead, mercury, arsenic, copper, cobalt, cadmium, and zinc, were also identified.…”
Section: Genome Announcementmentioning
confidence: 85%
See 1 more Smart Citation
“…Furthermore, phenol/toluene and chlorophenol degradation pathways were observed in IP26 T . Unlike the genome of S. indicum B90A T (2), the draft genome assembly of IP26 T was found to have a homogentisate degradation pathway. Genes encoding putative metal resistance/efflux proteins, including resistance proteins for lead, mercury, arsenic, copper, cobalt, cadmium, and zinc, were also identified.…”
Section: Genome Announcementmentioning
confidence: 85%
“…Gas-liquid chromatography-based HCH isomer degradation analysis (time dependent) revealed that IP26 T is a faster degrader of HCH isomers than the prototype bacterium Sphingobium indicum strain B90A T (2). …”
Section: Genome Announcementmentioning
confidence: 99%
“…It was revealed that PCR amplification was possible for the C23O genes of Sphingobium sp. YBL2 18) , Sphingobium indicum B90A 19) , and Sphingobium japonicum UT26S 20) , indicating that the primer set could detect the C23O genes of Sphingobium spp. capable of degrading aromatic and chloroaromatic compounds.…”
Section: Real-time Pcrmentioning
confidence: 99%
“…Members of this taxon are also known to be efficient degraders of hexachlorocyclohexane (HCH) isomers (13). In conformity with our primary objective, i.e., to elucidate the pangenomic variations across HCH-degrading genotypes, we have already sequenced two sphingomonads (4, 5). Both of their genomes represent species belonging to the genus Sphingobium (4, 5).…”
Section: Genome Announcementmentioning
confidence: 99%
“…In conformity with our primary objective, i.e., to elucidate the pangenomic variations across HCH-degrading genotypes, we have already sequenced two sphingomonads (4, 5). Both of their genomes represent species belonging to the genus Sphingobium (4, 5). We have sequenced the genome of yet another sphingomonad, belonging to the genus Novosphingobium , i.e., N. lindaniclasticum strain LE124 T , isolated from an HCH dumpsite (6).…”
Section: Genome Announcementmentioning
confidence: 99%